Lithuanian preschool teachers' pedagogical habitus of reading to children - Nijolė Bražienė; Daiva Malinauskienė (Institute of Social Affairs of the Pedagogical University of Cracow, 2023)
In Lithuania, the trend of parents not reading to their children is becoming evident. Understanding the importance of reading as the child's educational need, it is likely that the lack of reading to children in the family could be compensated by the environment of the preschool education institution, therefore, the aim of the presented research is to find out what the pedagogical habitus of the Lithuanian preschool teachers in reading to children is, i.e., teachers' attitudes and behaviour of reading to children. While using disguised observation and an informal conversational interview, three profiles of the teacher as a child-reader educator were identified and described in detail in the article: active reader educator, potential reader educator and passive reader educator. Referring to the findings of the study, it can be said that Lithuanian preschool education teachers lack knowledge about the child's literary education and practical skills on how to do it in a quality manner. Therefore, in the near future, to compensate for this, it is necessary to prepare and offer qualification improvement programmes on children's reading and literature issues to teachers of preschool education institutions. Nawyki pedagogiczne litewskich nauczycieli wychowania przedszkolnego w zakresie czytania dzieciom Na Litwie rośnie tendencja do nieczytania dzieciom przez rodziców. Rozumiejąc znaczenie czytania jako potrzeb rozwojowych i edukacyjnych dziecka, prawdopodobne jest, że brak czytania dzieciom w rodzinie może być zrekompensowany przez środowisko placówki wychowania przedszkolnego, a celem niniejszego badania jest zbadanie nawyków pedagogicznych litewskich nauczycieli wychowania przedszkolnego w zakresie czytania dzieciom, tj. postaw nauczycieli wobec czytania dzieciom i ich zachowań czytelniczych. Korzystając z ukrytej obserwacji i nieformalnych rozmów-wywiadów, zidentyfikowano i szczegółowo opisano w artykule trzy profile nauczyciela jako edukatora dzieci-czytelników: aktywny edukator czytelnika, potencjalny edukator czytelnika oraz pasywny edukator czytelnika. Na podstawie wyników badania można stwierdzić, że litewskim nauczycielom wychowania przedszkolnego brakuje wiedzy na temat literackiej edukacji dzieci i praktycznych umiejętności, jak ją prowadzić jakościowo. Aby zrekompensować to w perspektywie krótkoterminowej, konieczne jest zatem opracowanie i zaoferowanie programów doskonalenia zawodowego dla nauczycieli wychowania przedszkolnego w zakresie czytania dzieciom i literatury dziecięcej.